THE IMPLEMENTATION OF TOTAL PHYSICAL RESPONSE (TPR) METHOD TOWARDS ENGLISH LANGUAGE LEARNING ON AUTISM STUDENT AT AL-KHAIRIYAH SCHOOL FOR SPECIAL CHILDREN (SLB) CILEGON - Sintawati, Fairus (FKIP, UNIVERSITAS ISLAM SYEKH-YUSUF TANGERANG, 2023)
English is a language that used by people in the world. English can be learnt by students at school. This research aims to know the implementation of Total Physical Response (TPR) method towards English Language learning on Autism Student. The researcher used a case study with a qualitative descriptive approach. The method of data collection in this study is the observation method. The observations made by the researchers were participatory observations, and the researchers did not directly intervene with the object under investigation. The result of this research was TPR has been found suitable for early childhood use, TPR can also be used to teach English to children with autism. Children with autism have difficulty accessing learning content, such as lessons for non-autistic children. Autistic children usually have difficulty understanding spoken words relating to their language development. Keywords: learning, TPR, Autism Student